Creating bidirectional conduction block in the cavotricuspid isthmus by cryothermal ablation with a short freeze time: Insight from the results with a 2-minute freeze cycle. (1st December 2016) - Miyazaki, Shinsuke; Iwasawa, Jin; Taniguchi, Hiroshi; Nakamura, Hiroaki; Hachiya, Hitoshi; Matsuda, Junji; Takagi, Takamitsu; Watanabe, Tomonori; Hirao, Kenzo; Iesaka, Yoshito
Abstract: Background: Optimal freeze doses are unknown during cryothermal cavo-tricuspid isthmus (CTI) ablation. This study aimed to evaluate the feasibility of 2-minute freeze doses for CTI ablation. Methods: Forty-eight consecutive patients undergoing cryothermal CTI ablation following pulmonary vein isolation were enrolled. CTI ablation was performed with 2-minute freeze cycles and 8-mm tip cryocatheters. Results: Bidirectional CTI block was successfully achieved in 45(93.8%) patients with a median of 5.0[4.0–6.0] cryocatheter applications. The total procedure and fluoroscopic times were a median of 16.5[13.0–20.0] and 4.0[2.0–5.0] min, respectively. A crossover to radiofrequency was performed in 3 patients including 1 due to coronary spasms during the cryoapplication. The tip temperature when block was achieved was a median of − 81.0[− 73.3 – − 84.0]°C. Application times from the start of the last application to achieving block were significantly longer in patients with acute conduction resumption than in those without (46.8 ± 4.0 vs. 20.2 ± 8.8 s, p < 0.0001), and the optimal cutoff point for predicting no acute resumption was 38.5 s (sensitivity 100%, specificity 99.5%). Vasospastic angina occurred in 2 patients, during the procedure in 1 and after in another. Durability could be evaluated a median of 6.0[3.0–8.0] months after the procedure in 14 patients, and conduction resumption was observed in 8(57.1%). The majority of gaps were located at the inferior vena cava edge. Conclusions: Acute CTI block was obtained by 2-minute freeze cycles with short procedure and fluoroscopic times. Care should be taken to avoid coronary spasms during the peri-procedural period. Additional cryoapplications might be required to improve conduction block durability.